2018
DOI: 10.3390/ani8110187
|View full text |Cite
|
Sign up to set email alerts
|

Does the Optimal Dietary Methionine to Cysteine Ratio in Diets for Growing Chickens Respond to High Inclusion Rates of Insect Meal from Hermetia illucens?

Abstract: Simple SummaryCurrently, several alternative protein sources are under investigation for replacing soybean meal in poultry diets. One alternative is larvae meal of the black soldier fly (Hermetia illucens) with a specific sulfur amino acid composition. The larvae meal is limiting in sulfur amino acids supply and provides a wide methionine:cysteine ratio of 61:39. Currently, it is not known whether the insect meal has an impact on the optimal ratio of methionine to cysteine in broiler chicken diets. The methion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 71 publications
(132 reference statements)
0
24
0
1
Order By: Relevance
“…The synthesis of GSH in cells depends on the availability of the amino acid cysteine, which can be obtained directly from food or by metabolism of the essential amino acid methionine (Isaksson et al., 2011; Sikalidis et al., 2014). Animal proteins generally contain larger quantities of cysteine and methionine than plant proteins (Brede, Wecke, & Liebert, 2018; Wiesenborn, 2012). Thus, relative to omnivores, insectivorous birds could have a surplus of cysteine to relocate for cellular production of GSH.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of GSH in cells depends on the availability of the amino acid cysteine, which can be obtained directly from food or by metabolism of the essential amino acid methionine (Isaksson et al., 2011; Sikalidis et al., 2014). Animal proteins generally contain larger quantities of cysteine and methionine than plant proteins (Brede, Wecke, & Liebert, 2018; Wiesenborn, 2012). Thus, relative to omnivores, insectivorous birds could have a surplus of cysteine to relocate for cellular production of GSH.…”
Section: Discussionmentioning
confidence: 99%
“…The protein derived from this efficient insect is also rich in essential amino acids, and it showed an overall superior amino acid profile compared to soybean meal [5]. Furthermore, a recent study found that despite its high methionine: cysteine ratio (61:39), a complete replacement of soybean meal with BSF larva meal in broiler diets provided satisfactory outcomes without the need to modulate the optimal methionine: cysteine ratio [6]. But BSF larvae are not only a source of protein; in fact, they have a high fat content (up to 35%), and they are rich in minerals, among which Ca (5–8% dry matter -DM-) and P (0.6% to 1.5% DM) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Livestock husbandry practices have prompted an expanded use of synthetic amino acids in animal diets to enhance the performance and carcass quality of livestock, as well as to minimize the environmental impact caused by nitrogen excretion [1][2][3][4]. This is true for methionine, which is an essential amino acid for all livestock species, and it is the first limiting amino acid in diets for poultry and the second or third limiting amino acid in the corn-soybean meal diets for pigs [5,6].…”
Section: Introductionmentioning
confidence: 99%